Penerapan Sistem Budikdamber pada Pakan Probiotik Dalam Memperkuat Ketahanan Pangan di Era Covid-19 - Deri Malik; NO Rahmawati; O Puspitasari; D Aprilensia; P Annisa; Danang Yonarta (Pusat Unggulan Riset Pengembangan Lahan Suboptimal (PUR-PLSO) Universitas Sriwijaya, 2021)
Malik D, Rahmawati NO, Puspitasari O, Aprilensia D, Annisa P, Yonarta D. 2021. Application of the budikdamber system to probiotic feed in strengthening food security in the Covid-19 era. In: Herlinda S et al. (Eds), Prosiding Seminar Nasional Lahan Suboptimal ke-9 Tahun 2021, Palembang 20 Oktober 2021. pp. 476-481. Palembang: Penerbit & Percetakan Universitas Sriwijaya (UNSRI).Human needs for animal protein are increasing, but the availability of fish farming land is getting narrower. Fish farming also requires feed other than land, but fish feed is getting more expensive. Steps need to be taken to reduce feed costs and creativity for alternative cultivation areas, as well as apply appropriate techniques to meet animal needs in the Covid-19 era. This paper was to develop a bucket fish farming system on probiotic feed to increase food production in the community. The writing of this scientific paper uses a qualitative descriptive method. Descriptive method is a method used to create a sequential description of the relationship between the phenomenon under investigation and the results that are not expressed in numbers. Catfish rearing in 80 L bucket media for 30 days resulted in catfish SR 41–70%, fish harvest was 2440 g (71.76 g/head), and mustard harvest produced as much as 30 bunches. However, these results are not appropriate and it is still necessary to optimize the cultivation container in order to avoid death due to predators and fish that come out of the rearing container. The catfish cultivation system can be a potential solution for fish cultivation, especially in narrow areas and aquaponic vegetable growing media such as mustard greens as additional community food in the Covid-19 era.